Professional nurses and the dark side of work passion. Issue 4 (July 2016) - Bushardt, Stephen C.; Beal, Brent D.; Young, Marilyn; Khosla, Sanjana
Abstract : Obsessive passion can lead to burnout and work-life imbalance, harming your personal life, as well as causing negative effects for your organization.